A new species of Parapteronemobius from Zhejiang, China (Orthoptera: Trigonidiidae: Nemobiinae) - Ding, Nuo; Liu, Yi-Jiao; Liao, Xin-Yi; Shen, Chu-Ze; He, Zhu-Qing (Zootaxa, 2021)
Parapteronemobius contains 7 species or subspecies distributed in East Asia with only one species recorded from China. In this study, we reported the second species, P. chenggong He sp. nov., from Zhejiang. The new species differs from P. dibrachiatus in body size, male genitalia and COI gene. The phylogeny of this genus in subfamily Nemobiinae are discussed based on COI, 18S and 28S genes. The type specimens are deposited in the Museum of Biology, East China Normal University (ECNU).